The Roles of General Election Commission and General Election Supervisory Board for a Democratic Election - Suparman Marzuki (Jurnal Hukum IUS QUIA IUSTUM, 2008)
To build a strong  and reliable democratic institution, is a time  consuming process which also requires  a long patience.  Accordingly, three pillars of General Election Commission (KPU), namely, structural independency, functional independency and personal independency, shall be consistently  kept up and maintained.Keywords: General Election Commission, General Election Supervisory Board, Democratic